2021
DOI: 10.1155/2021/5631685
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Optimization of Higher Education Management System Based on Data Mining Technology

Abstract: In order to improve the low efficiency of higher education management and the unequal distribution of curriculum resources, facing the actual situation of higher education management, a higher education management system based on data mining technology is constructed and optimized. Using the correlation between MVC components of higher education management platform and the support of data mining technology, this paper constructs the MVC model 2 framework of higher education management platform which is a power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For mastered subject knowledge, it will be displayed with black filling in the learning cognitive map; for ungraspable subject knowledge, it will be displayed with gray filling. Meanwhile, subject knowledge with different levels of learning objectives will be regarded as different cognitive attributes, and will be displayed in six different grids in the learning cognitive map [15].…”
Section: Cognitive Objective Functions In the Educational Management ...mentioning
confidence: 99%
“…For mastered subject knowledge, it will be displayed with black filling in the learning cognitive map; for ungraspable subject knowledge, it will be displayed with gray filling. Meanwhile, subject knowledge with different levels of learning objectives will be regarded as different cognitive attributes, and will be displayed in six different grids in the learning cognitive map [15].…”
Section: Cognitive Objective Functions In the Educational Management ...mentioning
confidence: 99%
“…Literature [12] examined the current status of teaching resource data construction in higher education institutions and discussed methods to construct and optimize teaching resource databases in order to strengthen the functionality of teaching resource databases. Literature [13] introduced data mining technology into the construction and optimization of teaching management systems in higher education institutions, which realized the optimization and management of the database and provided helpful teaching resource database support and teaching services for teachers and students. Literature [14] investigated and analyzed the situation of students' utilization of teaching online resource libraries, and found that students search and answer questions on the resource library for the difficulties they encountered in learning is the most common.…”
Section: Introductionmentioning
confidence: 99%
“…In the new situation, the development of the Internet has greatly impacted people's working lives and society. In the process of society moving forward, education, as the foundation of the country, should be innovated and developed in the light of environmental changes to provide more appropriate education management for the new generation of students so that they can grow up quickly in a harmonious environment [11][12]. Colleges and universities should make innovations for the educational management of college students in the context of the Internet to further improve the overall quality of education.…”
Section: Introductionmentioning
confidence: 99%